Pengaruh Desain Produk dan Positioning Terhadap Keputusan Pembelian Coffeshop Tempat Peraduan Tegal - Sari Wiyanti; Lu’lu Khanin Naqiyah; Rosiana Nur Agustin; Dinda Refina Cantik (Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of product design and positioning on purchasing decisions at the Peraduan Tegal coffee shop. With the increasing competition in the coffee industry, it is important for business actors to understand the factors that influence consumer decisions. The research method used is quantitative, with data collection through questionnaires distributed to customers. The results of the study indicate that product design has a significant influence on purchasing decisions, with a t-test value showing positive results. In addition, positioning has also been shown to have a significant influence on purchasing decisions. This study concludes that the combination of attractive product design and the right positioning strategy can increase consumer purchasing decisions at the Peraduan Tegal Coffee Shop.